Gondolatok a szocialista telephelyelmélet megfogalmazásához - Barta, Györgyi (Tér és Társadalom, 1994)
What could be the explanation for the failure of exploring the theoretical connections between the socialist system and the practice of the choice of location so far? Why have we proved unsuccessful so far in exploring what general aspects have affected the choice of certain locations, the spatial distribution of the industry and the transition of that? It is not surprising that before the publication of János Kornai’s famous book called A hiány (The Absence, 1980) there had not been a socialist location theory, since the elaboration of that requires competence on the general function mechanism of the socialist system, the system of the power and property relationships and the decision mechanism that is formed as a consequence of this. It is János Kornai’s work again that made the connection of the micro- and macro-spheres in the socialism, i. e. the socialist type relationship between the companies and the state evident. This study attempts to build up the socialist location theory from some elements of János Kornai’s theory describing the socialist system. As a consequence of this a hypothesis was stated which says that the mechanisms of the socialist system generated regional processes of opposite direction. Among these the dominant regional process led to the conservation, or at least the extremely slow transition of the spatial structures. A great part of our present problems can be connected to our socialist legacy. Without being familiar with the regularities of the socialist system we cannot understand why the northern Hungarian region that had been the most industrialised area of the socialist era became a crisis region, why the Great Plain region where so "successful" industrial development had taken place in the 1960s and 1970s turned to an underdeveloped region at an extremely rapid pace, and why the signs of dynamic development can only be seen in Budapest and the northern part of Transdanubia.